Development of Digital Media for Sundanese Culture-Based Dakon Games to Improve Early Childhood Science Literacy - Roostin, Erna (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2025)
This study aims to develop the Dakon game into a digital Android-based game, Smartda (Smart Dakon), to enhance science literacy in early childhood. The research employs the Research and Development (R&D) method with the Borg & Gall model combined with the ADDIE model for game media development. The subjects involved 111 children and 7 teachers. The research instruments included questionnaires, interviews, and structured observations. Furthermore, the data were analyzed using qualitative and quantitative descriptive. The results show that: (1) The game media development process was reconstructed into a conceptual model, procedural model, and physical model in the form of a Smartda digital application and a Smartda game guidebook. (2) The Smartda game is feasible for improving early childhood science literacy, validated by expert tests with minor revisions and declared highly feasible by three validators. (3) The Smartda game model is quite effective in enhancing science literacy in early childhood, potentially impacting the development of all aspects of early childhood development.